2008
DOI: 10.1002/app.26619
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(acryloxyethyl‐trimethylammonium chloride‐co‐2‐hydroxyethyl methacrylate): A study of its interaction with sodium alginate

Abstract: Poly(acryloxyethyl-trimethylammonium chloride-co-2-hydroxyethyl methacrylate) [poly(Q-co-H)] was prepared by free radical polymerization in aqueous solution at 608C using potassium persulfate as initiator. Spectroscopic characterization confirmed the formation of poly(Q-co-H) and the molar fractions of acryloxyethyl-trimethylammonium chloride monomer units incorporated in the copolymers were determined by potenciometric titrations. The monomer reactivity ratios for Q and H are found to be r Q 5 0.04 6 0.01 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…Thus, when the microparticles are placed in simulated fluid medium their inner sponge structure rapidly absorb fluid medium, facilitating Cefazolin diffusion and release. A similar morphology for alginate–chitosan microparticles was observed by Acosta et al37 and system reported in previous publication using SEM 24…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, when the microparticles are placed in simulated fluid medium their inner sponge structure rapidly absorb fluid medium, facilitating Cefazolin diffusion and release. A similar morphology for alginate–chitosan microparticles was observed by Acosta et al37 and system reported in previous publication using SEM 24…”
Section: Resultssupporting
confidence: 88%
“…For this purpose the feed monomer composition of Q/H = 95/5 wt %, that corresponds to 92/8 mol %, was used. Copolymerization of these two monomers was detailed investigated previously and it was shown that this ratio between Q and H was optimum for synthesis of the copolymer with the highest concentration of quaternary ammonium (cationic) units in the polymer chain 24,25…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The poly(acryloxyethyl‐trimethylammonium chloride‐ co ‐2‐hydroxyethyl methacrylate) copolymer (poly(Q‐ co ‐H)) was prepared by free radical polymerization of the mixture of corresponding monomers (i.e., Q and H) in aqueous solution without the use of any crosslinking agent by a previously described procedure 15, 16. The polymerization was carried out for 48 h at 60°C that permitted to achieve high (>90%) conversions.…”
Section: Methodsmentioning
confidence: 99%
“…The hydrophilic permanently charged quaternary ammonium groups provide good water solubility, and the solution properties correspond to those of a strong polyelectrolyte 13, 14. Recently, poly(Q‐ co ‐H)/NaAlg complexes have been proposed as scaffolds for drug delivery and tissue regeneration 15, 17…”
Section: Introductionmentioning
confidence: 99%